Letters from Heaven: Popular Religion in Russia and Ukraine - Himka, John-Paul; Zayarnyuk, Andriy (University of Toronto Press, 2006)
An important contribution to the fields of religion and Eastern Slavic studies, this volume challenges readers to rethink old pieties and to reconsider the function of religion.